BIM in the Construction Industry - Cha, Hee Sung; Jiang, Shaohua (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains 19 peer-reviewed papers on the subject of BIM in the construction industry. These articles cover recent advances in the development of BIM technologies and applications in the field of architecture, engineering, and construction (AEC) industry.